Interventional effects of exercise on neuropathy in patients with diabetes: a systematic review with meta-analysis - Vanphuc Nguyen; Quangngoc Dinh; Fen Yu; Shuqi Jia; Xing Wang (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective This study aims to systematically evaluate the effects of exercise interventions on neurological dysfunction in diabetic patients, addressing inconsistencies in existing research. It seeks to clarify the impact of different exercise parameters and patient characteristics on nerve function improvements, providing evidence for optimized intervention strategies. Methods A search was conducted using PubMed, Web of Science, The Cochrane Library, and Embase databases for randomized controlled trials related to exercise interventions for neurological dysfunction in diabetic patients. The quality of the included studies was assessed according to the Cochrane Handbook for Systematic Reviews. The study utilized RevMan 5.3 to determine effect sizes and assess heterogeneity. Stata 17.0 was employed to evaluate publication bias in the included studies. Results The analysis incorporated 9 randomized controlled trials. The meta-analysis demonstrated that exercise leads to improvements in neurological dysfunction among diabetes patients (SMD = 0.61). Subgroup analysis revealed that an 8-week exercise regimen with moderate intensity was particularly effective in enhancing neurological function (SMD = 1.82, 1.58). Improvements were more pronounced in lower limb nerve conduction velocity (SMD = 0.60), peroneal nerve conduction velocity (SMD = 0.86), and sensory nerve conduction velocity (SMD = 0.59). Patients with a disease duration of 5 years or less showed significant improvement (SMD = 0.62). Conclusion Exercise effectively improves neurological dysfunction in diabetic patients, with an 8-week, moderate-intensity program showing the greatest benefits, particularly in lower limb and sensory nerve conduction velocity. These findings offer evidence-based guidance for clinical intervention and future research. Registration and proposal This study was registered with PROSPEO under No. CRD42024586981; the proposal is available at www.crd.york.ac.uk .